Reimagining Pokhara: Destination Branding, Cultural Transformation, and the Promise of Sustainable Tourism - Pahari, Deependra (Kalika Journal of Multidisciplinary Studies, 2025)
Pokhara, the newly proclaimed tourism capital of Nepal, is widely celebrated for its natural splendor, cultural vibrancy, and adventure offerings. With panoramic views of the Annapurna range, tranquil lakes like Phewa and Begnas, and a blend of ethnic traditions, Pokhara continues to attract both domestic and international tourists. However, despite its strong appeal, the city’s tourism branding remains fragmented, outdated, and often reactive rather than strategic. The rapid commercialization of tourism, combined with unregulated development and cultural commodification, has led to visible socio-cultural dissonance, eroding local identity and creating discontent within indigenous communities. This paper aims to explore how Pokhara can reposition itself through strategic destination branding grounded in sustainability, cultural authenticity, and inclusive governance. Using qualitative methods, the research draws insights from 75 tourists, 75 tourism entrepreneurs, one focused group discussion (FGD), and seven expert interviews, including representatives from the Nepal Tourism Board (NTB), Gandaki Province Government, Pokhara Tourism Council, and tourism academia. Through thematic analysis, visual data representation, and literature synthesis, the paper proposes an Integrated Destination Branding Model (IDBM) that emphasizes community participation, experiential storytelling, and digital transformation. The findings underscore the need for unified brand governance through a Destination Management Organization (DMO), improved tourism infrastructure, and sustainable practices that balance development with preservation. The paper concludes that Pokhara’s global competitiveness in tourism depends on a reimagined branding approach-one that is rooted in local values, inclusive of its people, and aligned with global sustainability trends.